Tariffs, transportation, and profits in cross-border e-commerce: A dual-channel supply chain decision-making strategy. - Yihang Guo; Xianle Wang; Zhongwei Yang; Kaimin Chen; Wei Weng (PLoS ONE)
The development of cross-border e-commerce platform promotes the new channel model between domestic and international. How to determine the dual-channel pricing decision of manufacturers and retailers under the condition of tariff and transportation heterogeneity has become an important and realistic problem. Based on the perspective of cross-border e-commerce dual-channel supply chain, this paper considers the impact of import tariff, transport heterogeneity and export tax rebate, compares and analyzes the performance difference between decentralized decision-making and centralized decision-making, and analyzes the impact of import tariff, export tax rebate and transport heterogeneity on cross-border e-commerce dual-channel pricing, demand and profit. The results show that the tariff is positively correlated with the manufacturer's direct selling price and the retailer's retail price, while the tariff is negatively correlated with the wholesale price, the demand and profit of direct selling channel and the retail channel. Export tax rebate rate is positively correlated with manufacturers' demand and profit and retailers' demand and profit, and negatively correlated with manufacturers' wholesale price, direct selling price and retail price. The increase of unit freight in direct channel is unfavorable to manufacturers and beneficial to retailers; The increase in unit freight rates in retail channels is bad for both manufacturers and retailers. Centralized decision-making is beneficial to supply chain demand and profits, and can improve the overall performance of the supply chain.